PENGARUH TAYANGAN FASHION DARI INTERNET TERHADAP HASIL BELAJAR DESAIN BUSANA - Elsa Dewi Iriyanti (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2017)
The purpose of the research is to know (1) the intensity effect of seeing fashion show from internet to learning result, (2) intensity of viewing fashion show from internet, and (3) learning result. The type of research used ex-post facto. The sampling technique using Simple Random Sampling, with Slovin formula. Data collection by questionnaires and documentation methods. Validity used Product Moment and reliability used Cronbach Alpha. Data analysis technique used descriptiv analysis and hypothesis test using Product Moment and it was started by normality and linearity test. The study shows that (1) there was a positive and significant between intensity effect of viewing fashion show from internet and learning result, gave a contribution fashion show from the internet to learning result of 44.5%, while the remaining 55.5% influenced by other factors; (2) the intensity of viewing fashion show from the internet in fair categories; (3) learning result in fair category.Key words: seeing fashion show from internet, learning result.